Legal research - Stott, David J (Essential legal skills, 1993)
Designed to give a grounding in effective communication, research and problem-solving skills, the Legal Skills series aims to blend theory and practice by encouraging the reader to think through particular problems. Each book provides a theoretical framework for understanding the specific skills, reinforcing this with practical exercises to develop the reader's grasp of how these skills are used. The skill of legal research is central to the everyday work of lawyers. This book describes three stages in the process of legal research: planning, implementation and presentation. It details the standard research bibliographies and introduces standard practitioners' research works.